Madres comunitarias antioqueñas y su vocación por el cuidado (2016)
ABSTARCT: This article deals with the issue of becoming community mother for the government program of the Colombian Family Welfare Institute. The objective is to recognize the meaning that has for the community mothers their joining to the program of Welfare Homes. The scope of this study is to widen the vision about the work of care performed by the community mothers of Antioquia. A qualitative methodology was used, with a phenomenological-hermeneutical method. The sample was constituted by 30 community mothers coming from 6 municipalities of Antioquia department (Colombia) which participated in detailed surveys and focus groups. The research results show that is different to be a community mother than becoming a community mother; and that there are different ways, motivations and conditions to become a community mother; and that the work performed by these women promotes both their subjectivation and this of the children attending their homes. When care is performed by vocation it turns itself into an ethical practice.